THE EFFECT OF EARNING PER SHARE (EPS), NET PROFIT MARGIN (NPM) AND RETURN ON ASSET (ROA) ON STOCK PRICE IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD - RISMA RISMA (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This study aims to determine the effect of Earning Per Share, Net Profit Margin and Return On Assets on Stock Prices in Banking Companies Listed on the Indonesia Stock Exchange for the 2018-2020 period. This research was conducted at banking companies listed on the Indonesia Stock Exchange, totaling 46 companies and taking samples using a purposive sampling technique, which met the criteria of 42 companies. Methods of data collection using the method of documentation, literature and the internet. The data analysis used was SPSS V23, while the data management was the classical assumption test, multiple linear regression analysis and hypothesis testing. From the results of research using the coefficient of determination test (R2) obtained a yield of 76.3%. Earning Per Share, Net Profit Margin and Return On Assetsjointly affect the stock price, while the remaining 23.7% is influenced by other variables not examined in this study. From the results of the multiple linear regression test results obtained the regression equation Y = (182.534) + (5.667) X1+ (0,881) X2+ (0,780) X3, based on the results of the t (partial) test for the Earning Per Share variable has tcount>ttable or 7,218 > 2,00324 then H0 rejected and Ha accepted so it can be concluded that Earning Per Share has a significant effect on Stock Price, Net Profit Margin has tcount<ttableor 0.535 < 2.00324 then H0 accepted and Ha rejected so it can be concluded thatNet Profit Margin no significant effect on the stock price, andReturns On Assethave tcount>ttableor 2,416 > 2,00324 then H0 rejected and Ha accepted so it can be concluded thatReturn On Asset positive and significant effect on stock prices. And from the F test (simultaneous)Earning Per Share, Net Profit Margin dan Return On AssetFcount>Ftableor 60.019 > 2.54 so it can be concluded, simultaneously has a positive and significant influence on stock pricesBanking Companies Registered On The Indonesia Stock Exchange 2018-2020 Period